Content Analysis of the Articles Published in the Ethiopian Sport Science Journal (EJSS) from 2020 through 2023 - Assefa, Abera; Eshau (Ph.D), Abebe; Abera, Bekagn (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2024)
This study analysis the content of 45 research papers published in the Ethiopian Journal of Sport Science (EJSS), affiliated with the Ethiopian Sport Academy. The papers were retrieved from the African Journals Online platform (AJOL), for their complete article and abstract accessibility. In this study, content analysis was employed considering the following four key dimensions: 1) Subjects covered and units of analysis 2) Methodology and Design3) Authorship and collaboration and 4) Types of papers or formats and numbers of papers’ per volume. The findings of the study revealed that the papers included in the four volumes primarily centered on exercise physiology and sport pedagogy at the sport ‘team level’ units of analysis. Quantitative research methods were predominantly used across various sports science disciplines, with limited representation of pure qualitative and mixed-methods studies. Additionally, while most research lacked clearly stated conceptualizations, a considerable number of papers did include research objectives. It was also noted that the majority of authors were male individuals working independently from universities. Therefore, the study highlights the potential of a journal to become a leading platform for disseminating innovative research in sports and physical education, particularly in Ethiopia. The findings suggest that some amendments may be necessary.